The commercialisation of news and editorial freedom: a study of Buletin Utama TV3 / Harmi Taazim Mohamad - Mohamad, Harmi Taazim (Institute of Graduate Studies, UiTM, 2017)
This qualitative study is focusing on the commercialisation of news in Buletin Utama, TV3. Researcher concerned is to investigate how to balance the news reporting based on the journalism principle in combine with the paid news content to serve public interest. Do the media practitioners concern and realise that this may cause to certain implications to the newsroom culture and news credibility. Therefore, this study is to understand several research questions as per below query: (i)To what extent has the commercialisation of news items duration in Buletin Utama affected the space of editorial content?(ii)Who are the advertisers that had consume the commercialisation of news duration in place of editorial content in Buletin Utama?(iii) Are there any restraint forces for editors of Buletin Utama in maintaining editorial independence from the providers of financial support?(iv)How does Buletin Utama manage a creative negotiation to ensure credibility of news stay intact and at the same time serve the stake holders and to ensure survival in the 21st century? Firstly, the study focused on the durations of the commercialization of news items in Buletin Utama. By using content analysis, the researcher collected the data from the three years of Buletin Utama. The findings showed that there are 6,075 commercialization of news in Buletin Utama for the year 2007, 2008 and 2010.